Prognostic impact of p16 and PD-L1 expression in patients with oropharyngeal squamous cell carcinoma receiving a definitive treatment - Sato, Fumihiko (J Clin Pathol, 2019)
AIMS: Limited information is available regarding the precise differences in the tumour immune microenvironment (TIM) of patients with human papilloma virus (HPV)-associated and non-HPV-associated oropharyngeal squamous cell carcinoma (OPSCC). Here, we retrospectively reviewed 137 patients with OPSCC treated with a definitive treatment to identify molecular relationships in the TIM. MATERIALS AND METHODS: We used immunohistochemical analysis to assess p16 status, programmed death ligand 1 (PD-L1) level, and/or CD8(+) tumour-infiltrating lymphocyte (TIL) density, followed by prognostic evaluation of these immune-related parameters. RESULTS: Multivariate analyses demonstrated that PD-L1 level on immune cells but not on tumour cells or CD8(+) TIL density was a significant predictive factor of disease-free survival (DFS) and overall survival (OS). Additionally, subgroup analyses demonstrated that patients positive for p16 and PD-L1 expression on immune cells had favourable DFS and OS, whereas patients negative for p16 and PD-L1 expression on immune cells showed worse DFS and OS. CONCLUSIONS: We demonstrated that PD-L1 expression on immune cells but not tumour cells might represent a useful prognostic biomarker in patients with OPSCC receiving a definitive treatment. We propose that a co-assessment of p16 and PD-L1 expression on immune cells would have greater prognostic potential compared with evaluation of each factor alone in patients with OPSCC.